Pengaruh Lokasi dan Kepercayaan Terhadap Keputusan Pembelian Herbal Chicken Ciawi - Rossana Sapta Kusumah; Suci Rahmawati; Agung Darmawan; Siti Nadya Safira; Muhamad Nauval Ardani; Firmansyah Firmansyah (MANAJEMEN, 2025)
This study aims to analyze the influence of location and trust on purchasing decisions for Herbal Chicken Ciawi products. The method used is a quantitative approach with a descriptive-explanatory design. The research sample consisted of 57 respondents selected through purposive sampling, and the data were analyzed using multiple linear regression. The results show that trust has a significant effect on purchasing decisions, while location has no significant effect. However, both variables simultaneously have a significant influence. These findings confirm that consumer trust is more dominant than location in influencing purchasing decisions. The practical implication of this study is that business owners need to focus on building trust by improving service quality, ensuring product consistency, and strengthening brand image.